2021
DOI: 10.3390/life11060506
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Brain Imaging Suggests Changes in the Availability of mGluR5 and Altered Connectivity in the Cerebral Cortex of Long-Term Abstaining Males with Alcohol Dependence: A Preliminary Study

Abstract: Direct in vivo evidence of altered metabotropic glutamate receptor-5 (mGluR5) availability in alcohol-related disorders is lacking. We performed [11C]ABP688 positron emission tomography (PET) and resting-state functional magnetic resonance imaging (rs-fMRI) in prolonged abstinent subjects with alcohol dependence to examine alterations of mGluR5 availability, and to investigate their functional significance relating to neural systems-level changes. Twelve prolonged abstinent male subjects with alcohol dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Interestingly, Maillard et al [176] found a hypermetabolism in the cerebellum and hippocampus of persons with AD who relapsed within 6 months and additionally in the anterior cingulate cortex of persons with AD who relapsed after 12 months. Further (preclinical) multimodal studies combining PET and MRI in AD investigated glutamatergic but not DA neurotransmission in animal models [177, 178].…”
Section: Correlations With Other Imaging Results (Fmri Mrs)mentioning
confidence: 99%
“…Interestingly, Maillard et al [176] found a hypermetabolism in the cerebellum and hippocampus of persons with AD who relapsed within 6 months and additionally in the anterior cingulate cortex of persons with AD who relapsed after 12 months. Further (preclinical) multimodal studies combining PET and MRI in AD investigated glutamatergic but not DA neurotransmission in animal models [177, 178].…”
Section: Correlations With Other Imaging Results (Fmri Mrs)mentioning
confidence: 99%
“…Despite numerous differences in the study populations, taken together this suggests that the higher mGlu5 receptor availability identified in the present sample may be characteristic of an early abstinence period. Thus the 4‐week time point may not have been long enough to observe significant change (Camchong et al, 2013b; Joo et al, 2021). Smoking may also influence these relationships given its effects on mGlu5 receptor availability; though there were no significant effects of smoking on connectivity outcomes or PET‐fMRI relationships in these analyses, the power to detect these was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is little evidence in these data that connectivity differences change toward control levels within the first month of abstinence. However, a report of mGlu5 receptor availability and functional connectivity in men with AUD (67% smokers) abstinent from alcohol >2 years identified clusters of lower BP ND in the abstinent AUD group in temporal and parietal cortices compared to healthy controls (Joo et al, 2021). Seed‐based analyses identified an area in the parietal cortex with lower mGlu5 availability in the AUD patients that also had higher functional connectivity with occipital cortex compared to healthy controls, while network and global connectivity were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antagonism of the metabotropic GLU receptor, mGluR5, prevented alcohol induced relapse in rats ( Adams, Short, & Lawrence, 2010 ). Recent advances using positron emission tomography (PET) imaging have identified a link between mGluR5 availability (specifically cortical and mesolimbic) and long-term relapse in patients who abuse alcohol ( Ceccarini et al, 2020 ; Joo et al, 2021 ). Additionally, acute alcohol use inhibits the ionotropic GLU receptor NMDAR while chronic alcohol use upregulates NMDAR function.…”
Section: Alcoholmentioning
confidence: 99%